KELAYAKAN POWERPOINT BERBASIS FLASH STRUKTUR DAN FUNGSI JARINGAN PADA TUMBUHAN DI KELAS XI SMA - Widyarsih, Nia; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aimed to determine the feasibility of flash-based powerpoint (flash PPT) learning media on material structure and function of plans in class XI. The research methode was descriptive. Flash PPT learning media developed from the results of research stomata sizes and types. Flash PPT media was conducted using Yamasari by media expert validators and learning material experts. The results of flash PPT media validation study obtained a total average score of 3.56 which was classified as valid, so that flash PPT was suitable to be used in the material structure and function of plant tissue in class XI. Keywords: Feasibility, Flash-PPT, Structure, Plant, Tissue